2022
DOI: 10.47626/2237-6089-2021-0250
|View full text |Cite
|
Sign up to set email alerts
|

Well-being at work, productivity, and coping with stress during the COVID-19 pandemic

Abstract: This study aims to analyze the mechanisms through which the coronavirus disease (COVID-19) pandemic impacts on well-being at work and on productivity. The secondary objective is to identify stress management strategies for the work environment during the pandemic. This is an integrative review. Phase 1 consisted of searches of open access electronic databases (MEDLINE, SciELO, Bireme, and LILACS) for papers published in 2020 addressing mental health, work, and pandemics. Phase 2 consisted of selecting literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Many workers likely employ high levels of adaptive coping strategies, as their future prospects for a better quality of life are instrumental in attaining their goals and meeting their expectations. By examining the relationship between each coping strategy, psychological distress, and life satisfaction, this study will contribute to the existing literature in health psychology [5,27,28]. Previous studies conducted among workers have typically treated coping strategies as a unifying construct rather than considering them as multiple dimensions of mental health [25].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Many workers likely employ high levels of adaptive coping strategies, as their future prospects for a better quality of life are instrumental in attaining their goals and meeting their expectations. By examining the relationship between each coping strategy, psychological distress, and life satisfaction, this study will contribute to the existing literature in health psychology [5,27,28]. Previous studies conducted among workers have typically treated coping strategies as a unifying construct rather than considering them as multiple dimensions of mental health [25].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…At the beginning of the COVID-19 pandemic, many researchers assumed that it will cause mental health problems more frequently than usual and that will have effects on the different life circumstances even after the crisis ends. This paper specifically deals with the mental health in the occupational context, because previous research has shown that mental health issues among the employees are the most common causes of negative organizational outcomes such as lower productivity [13,27] and higher rates of absenteeism [14] that may cause economic costs. The results of this study have confirmed that employees from the Serbian sample are facing mental health issues during uncertain times [8].…”
Section: Discussionmentioning
confidence: 99%
“…This paper specifically deals with the mental health in the occupational context, because previous research has shown that mental health issues among the employees are the most common causes of negative organizational outcomes such as lower productivity [ 13 , 27 ] and higher rates of absenteeism [ 14 ] that may cause economic costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation